2019
DOI: 10.1017/jfm.2019.376
|View full text |Cite
|
Sign up to set email alerts
|

Direct numerical simulations of Taylor–Couette turbulence: the effects of sand grain roughness

Abstract: Progress in roughness research, mapping any given roughness geometry to its fluid dynamic behaviour, has been hampered by the lack of accurate and direct measurements of skin-friction drag, especially in open systems. The Taylor-Couette (TC) system has the benefit of being a closed system, but its potential for characterizing irregular, realistic, 3-D roughness has not been previously considered in depth.Here, we present direct numerical simulations (DNSs) of TC turbulence with sand grain roughness mounted on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…The findings presented in figure 3 show that the presence of the roughness affects the relative turbulence statistics in the bulk of the flow, far away from the roughness sublayer region (in contrast to homogeneous roughness in TC flow (Berghout et al 2018)), reminiscent to what is found in studies of pipe and channel flow (Koeltzsch et al 2002;Chung et al 2018). Figure 3(b) shows the axial variations of the friction factor c f (z) (see section 1) on both the inner cylinder and the outer cylinder.…”
Section: Response Of the Turbulent Taylor Vorticesmentioning
confidence: 95%
“…The findings presented in figure 3 show that the presence of the roughness affects the relative turbulence statistics in the bulk of the flow, far away from the roughness sublayer region (in contrast to homogeneous roughness in TC flow (Berghout et al 2018)), reminiscent to what is found in studies of pipe and channel flow (Koeltzsch et al 2002;Chung et al 2018). Figure 3(b) shows the axial variations of the friction factor c f (z) (see section 1) on both the inner cylinder and the outer cylinder.…”
Section: Response Of the Turbulent Taylor Vorticesmentioning
confidence: 95%
“…The results from Fig. 3.3 hints that the presence of the roughness might have an effect on the morphology of the flow, far away from the roughness sublayer region [133], on the order of the gap width d, and reminiscent to what is found in studies of pipe and channel flow [115,117]. To gain more insight into how the roughness alters the flow, we set out to measure the velocity field in the meridional plane using PIV at multiple heights.…”
Section: Response Of the Turbulent Taylor Vorticesmentioning
confidence: 83%
“…They attribute this to a dominance of the pressure drag over the viscous drag on the cylinders. Structure in the form of grooves in the streamwise direction were studied by Very recently, [133] studied the influence of sandgrain roughness in TC flow, and found similarity of the roughness function with the same type of roughness in pipe flow [134]. We highlight that none of the works described above, reported an influence of the roughness over the axial wavelength of the rolls.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…They attribute this to a dominance of the pressure drag over the viscous drag on the cylinders. Structure in the form of grooves in the streamwise direction were studied by Very recently, [203] studied the influence of sandgrain roughness in TC flow, and found similarity of the roughness function with the same type of roughness in pipe flow [204]. We highlight that none of the works described above, reported an influence of the roughness over the axial wavelength of the rolls.…”
Section: Introductionmentioning
confidence: 89%